2006
DOI: 10.1021/es0517973
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorochemicals in Pooled Serum Samples from United States Residents in 2001 and 2002

Abstract: Manufacturers have used perfluorochemicals (PFCs) since the 1950s in many industrial and consumer products, including protective coatings for fabrics and carpet, paper coatings, insecticide formulations, and surfactants. Some PFCs are persistent ubiquitous contaminants in the environment and in humans. Exposures to PFCs result in potential developmental and other adverse effects in animals. The sources of human exposure to PFCs and the potential health risks associated with exposure are still unclear, and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
132
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(153 citation statements)
references
References 44 publications
19
132
2
Order By: Relevance
“…In another occupational study, Kaplan (2004) did not report an association between HDL and serum PFOA concentrations. Neither did Emmett et al (2006a) in a community-based exposure study whose median PFOA concentrations (approximately 0.354 lg/ml) were 60 times higher than that of general population studies (Calafat et al 2006;Olsen et al 2003b). To further clarify any possible association with HDL, the A apolipoproteins, which form the major proteins found in HDL, could be measured although this was not part of the present study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In another occupational study, Kaplan (2004) did not report an association between HDL and serum PFOA concentrations. Neither did Emmett et al (2006a) in a community-based exposure study whose median PFOA concentrations (approximately 0.354 lg/ml) were 60 times higher than that of general population studies (Calafat et al 2006;Olsen et al 2003b). To further clarify any possible association with HDL, the A apolipoproteins, which form the major proteins found in HDL, could be measured although this was not part of the present study.…”
Section: Discussionmentioning
confidence: 79%
“…The widespread presence of PFOA in the blood of the general population (Calafat et al 2006) has resulted in assessments of sources of exposure including industrial production, indirect sources including atmospheric production, and transport of telomer precursors (De Silva and Maybury 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Haug et al (2009) reported that PFNA, PFDA, and PFUdA concentrations in serum increased with age. In contrast, in the NHANES study, in which 54 pooled serum samples of the 2001/2002 survey and 1562 serum samples of the 1999-2000 survey were analyzed, no association of PFCs concentrations with age was found (Calafat et al, 2006a;Calafat et al, 2007). Studies on a Chinese population around Bohai sea did not show any significant difference between two age groups (Guo et al, 2011).…”
Section: Age Effect On Pfcs Concentrationsmentioning
confidence: 80%
“…In recent years, PFCs especially perfluorooctanoic acid (PFOA) and perfluorooctanyl sulfonate (PFOS) have received much attention because they were ubiquitously detected in various environmental media [3][4][5][6][7][8][9][10][11] and in the body of wildlife [12,13] and human beings [14][15][16][17]. Though their sources, fate and transport in the environment are not well understood, it has been known that they are directly released into the environment or indirectly formed [18].…”
Section: Introductionmentioning
confidence: 99%